Evaluating the customers' dining attitudes, e-satisfaction and continuance intention toward mobile food ordering apps (MFOAs): Evidence from Bangladesh - Md Al Amin; Md Shamsul Arefin; Nayeema Sultana; Md. Rakibul Islam; Israt Jahan; Ayeasha Akhtar (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - This study was designed to specifically explore confirmation and perceived usefulness associated with mobile food ordering apps (MFOAs) in consideration of their impacts upon attitudes, satisfaction and intention to continuously use. Design/methodology/approach - The research utilized the convenience sampling to gather data from 250 respondents having prior experience with MFOAs during COVID-19 pandemic period in Bangladesh. The Structural Equation Modeling technique was applied to analyze the data using SmartPLS 3 software. Findings - This study's results showed that customers' perceived confirmation and usefulness were significant in determining their dinning attitudes. Besides, customers' dining attitudes were positively related to e-satisfaction. Finally, the customers' continuance intention to use MFOAs was significantly influenced by their e-satisfaction. Research limitations/implications - Restaurants managers should focus on online sales through MFOAs during the pandemic period since social distancing is a key strategy to manage COVID-19. Customers should be assured that the safety measures are undertaken while delivering the food. Originality/value - This study incorporated the expectation-confirmation theory and technology acceptance model and tested it in the context of MFOAs.
Keywords: 650; Confirmation; Continuance intention; Dining attitudes; E-satisfaction; Mobile food ordering apps (MFOAs); Restaurants